Micropatterned Elastic Gold‐Nanowire/Polyacrylamide Composite Hydrogels for Wearable Pressure Sensors. Issue 7 (7th June 2018) - Yin, Ming‐jie; Zhang, Yangxi; Yin, Zhigang; Zheng, Qingdong; Zhang, A. Ping
Abstract: Elastic hydrogels have recently attracted remarkable attention because of their unique mechanical and stimulus‐responsive properties. In this work, a novel elastic supramolecular hydrogel for wearable pressure sensors is developed by photocrosslinking polyacrylamide (PAAm) through covalent bonds and hydrogen bonds as well as ionic bonds in the presence of poly(acrylic acid) and Ca 2+ . Gold nanowires( Au NWs) are homogeneously mingled with the PAAm hydrogel to attain a conductive composite hydrogel. Using an in‐house optical maskless exposure technology, printable piezoresistive pressure sensors are quickly fabricated by directly patterning the composite hydrogel into microribs on flexible electrodes. The pressure sensors with microrib structures exhibit a bimodal contact mode between Au NWs, which provides a new pathway to engineer the sensor's sensitivity and operation range. In the experiments, the pressure sensor with optimized microrib structures shows not only ultrahigh sensitivity (i.e., 3.71 kPa −1 in the pressure range of 0–2.8 kPa) but also low detection limit (i.e., 0.2 Pa) and long‐term stability. A flexible hand‐shape electrode device and an arterial pulse monitoring sensor are demonstrated to reveal the potentials of such a pressure sensor on wearable device applications. Abstract : Micropatterned elastic composite hydrogels and their sensor applications are presented. Elastic supramolecular hydrogel is prepared by photopolymerization of acrylamide monomer in the aqueous solution of poly(acrylic acid) and CaCl2 . After mixing with gold nanowires, the composite hydrogel is in situ micropatterned on electrodes to fabricate wearable pressure sensors. Applications of the sensors in arterial‐pulse monitoring and E‐hand skin are demonstrated.